PENERAPAN ISAK 35 TERHADAP PENYAJIAN PELAPORAN KEUANGAN ENTITAS BERORIENTASI NONLABA PADA YAYASAN RA AMAL SHALEH - Diningsih, Sintia Agus; Yuliarti, Norita Criitra; Maharani, Astrid (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
The Ra Amal Shaleh Tempurejo foundation is a non-profit oriented foundation which means it is no for profit and is engaged in Islamic-based education with Raudatul Atfal (RA) level. The soures of income for the ra amal shaleh faoundation com from donation froms, the community, the government (BOP) and income from tuition fees from students. The Ra Amal Shaleh foundation only make reports in the form of cash in and cash out every month and funds originating from government will be reported in accordance with the technical guidelines for financial reports. The purpos of this study is to apply financial standards, namely referring to the interprestation of financial accounting standards (ISAK) 35, which contain statements of financial position, reports of comprehensive income, report of net asset, report of cash flows, and notes to financial statements. This study uses a qualitative method with a descriptive approach in order to explain everything that exists in the transaction that occur at the foundation. The result of study explain that the foundation has not implemented ISAK 35 in the preparation of financial statements. This research has recrontructed the financial statements of Ra Amal Shaleh foundation based on ISAK 35.